Antifungal activity of chitinase obtained from Paenibacillus ehimensis MA2012 against conidial of Collectotrichum gloeosporioides in vitro. (July 2016) - Seo, Dong-Jun; Lee, Yong-Sung; Kim, Kil-Yong; Jung, Woo-Jin
Abstract: To investigate the expression patterns of chitinase on SDS-PAGE gel, Paenibacillus ehimensis MA2012 was incubated in gelatin-chitin medium (GCM) at 30 °C for 7 days. Six major bands (Ch3, Ch4, Ch5, Ch6, Ch7, and Ch8) of chitinase isozymes in GC medium appeared on SDS-PAGE gel during the incubation period. Chitinase activity staining of P. ehimensis MA2012 was detected on 2-DE with different pI values (4–11). After DEAE-Sephadex chromatography, eight bands (Ch1 to Ch8) of chitinase isozymes were stained strongly with Calcofluor white M2R at fraction 45. After Sephadex G-75 gel filtration, six bands (Ch3 to Ch8) of chitinase isozymes were stained with Calcofluor white M2R at fractions of 11–12. The specific activity of the purified chitinase was 3.8 units mg −1 protein with a purification factor of 0.27. Inhibition rate of the conidial germination of Colletotrichum gloeosporioides was 87% in partial purified chitinase treatment compared with control. Highlights: Paenibacillus ehimensis MA2012 was incubated in gelatin-chitin medium (GCM). Six major bands (Ch3, Ch4, Ch5, Ch6, Ch7, and Ch8) of chitinase isozymes appeared on SDS-PAGE gel. Chitinase activity staining of MA2012 was detected on 2-DE with different pI 4–11. Inhibition rate of the conidial germination of Collectotrichum gloeosporioides was 87% in chitinase treatment.